More than Vestiges: Photographic Archives of Ancient Mexico (Glocalism: Journal of Culture, Politics and Innovation, 2021)
This article explores the importance of photographic archives (fototecas) in preserving the sources with which to create a national visual history and identity. It charts the arc from imperial photography of Mexico, lodged in European and U.S. archives, to the development of Mexican institutions dedicated to the preservation of the photographic patrimony. Particular attention is paid to the photography of indigenous peoples by foreigners and Mexicans, and the location of the archives in which that imagery is held. Some of the archives mentioned are found in Mexico: Archivo General de la Nación, the Fototeca Nacional-Instituto Nacional de Antropología e Historia (INAH), the Museo Nacional, and the Instituto Nacional de los Pueblos Indígenas (INPI). Others are located elsewhere: the Smithsonian Institute, the Getty Museum, the Musée du Quai Branly-Jacques Chirac, American Museum of Natural History, and the Museum of Cultural History in Oslo. Among the photographers mentioned are: Desiré Charnay, León Diguet, Teoberto Maler, Frederick Starr, Carl Lumholtz, Julio de la Fuente, and Nacho López.
Keywords: photographic archives; Native Americans; Mexico; Indigenismo; Indianism; imperial photography